Barriers and strategies for scaling up livestock agroforestry systems in the Colombian amazon piedmont - Solarte, Antonio; Rico, Adrián; Zapata, Catalina; Chará, Julián; Murgueitio, Enrique (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Silvopastoral systems (SPS) are sustainable livestock production systems with multiple benefits. Nevertheless, its adoption has been limited. Objective: To identify the barriers encountered by farmers to adopt SPS, considering the perceptions of producers and the strategies to promote its adoption as a tool for sustainable cattle ranching in the Amazonian foothills of Caquetá province, Colombia. Methods: Experts on sustainable cattle ranching from public and private organizations implementing projects in Caquetá were called to contribute to participatory rural appraisal workshops and focus groups. In these workshops also participated producers from the south of the province with three to five years of experience in establishment SPS, and producers from north of the province who were just starting with SPS. Results: The experts recognized 13 practices promoted by institutions for sustainable cattle ranching. These alternatives were categorized into pasture management, livestock agroforestry, conservation, and renewable energy systems. They also identified 21 barriers that limit the adoption of these alternatives, which were grouped into skills and knowledge, social, economic, environmental, and technical and operational barriers. The cattle farmers prioritized and established the advantages and disadvantages of the four main SPS. In response to the barriers, 22 scaling-up strategies were identified and classified into five categories contributing to promote the adoption of SPS. Conclusions: Organizations promoting sustainable practices for cattle ranching and farmers in the Caquetá foothills recognize the importance of SPS, but there are still barriers related to knowledge, implementation costs, environmental, and cultural conditions that need to be addressed to increase its adoption.